2016
DOI: 10.1136/neurintsurg-2015-012218
|View full text |Cite
|
Sign up to set email alerts
|

Time to redefine success? TICI 3 versus TICI 2b recanalization in middle cerebral artery occlusion treated with thrombectomy

Abstract: Neurologic outcome is substantially better in TICI 3 than TICI 2b patients, and hospital stays are shorter. Endovascular strategies that consequently strive to achieve TICI 3 may be warranted and cost-effective, and should be examined by future research. TICI 3 rates should be included as a safety measure in studies evaluating MTE devices and techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(135 citation statements)
references
References 23 publications
9
125
1
Order By: Relevance
“…Our results among low NIHSS stroke patients are in accordance with the recently described strong links between successful reperfusion and favourable functional outcome in AIS patients with moderate-to-severe stroke enrolled in recent RCT [24,25,26]. …”
Section: Discussionsupporting
confidence: 79%
“…Our results among low NIHSS stroke patients are in accordance with the recently described strong links between successful reperfusion and favourable functional outcome in AIS patients with moderate-to-severe stroke enrolled in recent RCT [24,25,26]. …”
Section: Discussionsupporting
confidence: 79%
“…TICI 2b implies residual perfusion deficits which are, albeit confined to relatively small territories, relevant for the infarct severity in this area, and consequently for subsequent HTs [9,10]. This observation once more underlines the notion that potentially more aggressive approaches to achieve TICI 3 may be of benefit [26]. …”
Section: Discussionmentioning
confidence: 95%
“…Scores were assessed by an experienced vascular neurologist. NIHSS score <5 was defined as good neurologic outcome [26], while substantial neurologic improvement was defined as a compound criterion of either NIHSS at discharge of ≤1 or difference between baseline NIHSS and NIHSS at discharge of ≥8. Patients who died during their stay at the hospital were assigned to a score of 42 [27].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Kleine et al reported that compared with almost complete reperfusion (TICI 2b), complete reperfusion (TICI 3) was associated with significantly greater neurologic recovery and better neurologic outcomes (37% versus 68%). 11 Although not significant, Yoo et al likewise observed a higher rate of good functional outcomes (mRS of 0-2 at $90 days) in patients with a TICI 3 grade compared with patients with a TICI 2b grade (62% vs. 46%). 12 The present results are in agreement with the results of these prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 69 included patients, 35 (50.7%) had atrial fibrillation, 36 (52.2%) had hypertension, and 15 (21.7%) had diabetes mellitus. The patients' mean DWI-ASPECTS was 7.5 (range, [3][4][5][6][7][8][9][10][11]. Among the 69 patients, the occluded vessel was the ICA in 24 patients (34.8%), the MCA M1 portion in 41 patients (59.4%), and the MCA M2 portion in 4 patients (5.8%).…”
Section: Baseline Characteristics Of the Patientsmentioning
confidence: 99%